Dissertation Research on Pedagogy: Situation, Problems, Resources - E. B. Vesna; V. V. Serikov (Высшее образование в России)
In the article the situation and trends in the development of dissertations in pedagogy have being analyzed, positive trends and reasons for the low quality of individual dissertations is indicated. The authors focus on methodological “omissions” that reduce the scientific value of dissertations. Authors include to that the construction by dissertators of key theoretical and methodological premises of the study – a research question, a hypothesis, a concept, novelty, a model of the process under study, an experimental substantiation of the conclusions, which reflect the “deficiencies” of the methodological culture of authors, the specifics of pedagogical research are not taken into account. The authors try to explain why these “conclusions” often cause mistrust among practicing teachers. Constructive recommendations for conducting a dissertation research are also made in the article.